Sexuality Education in Brazilian Medical Schools. (1st May 2014) - Rufino, Andrea Cronemberger; Madeiro, Alberto; Girão, Manoel João Batista Castello
Abstract: Introduction: Sexuality education has been valued since the 1960s in medical schools worldwide. Although recent studies reaffirm the importance of incorporating sexuality into medical education, there are data gaps concerning how this happens in Brazil. Aim: To understand how Brazilian medical school professors teach sexuality in undergraduate courses. Methods: An exploratory, cross‐sectional descriptive study was conducted. A total of 207 professors from 110 Brazilian medical schools responded to an online semistructured questionnaire about the characteristics of the sexuality‐related topics offered. Main Outcome Measures: The main variables assessed were contact hours devoted to sexuality, disciplines in which sexuality topics were taught, sexuality‐related course titles, and sexuality‐related topics addressed. Questionnaires were tabulated and analyzed using descriptive statistics for frequency distribution. Results: The response rate to the questionnaire was 77.2%. Almost all professors (96.3%) addressed sexuality‐related topics mainly in the third and fourth years as clinical disciplines, with a 6‐hour load per discipline. Gynecology was the discipline in which sexuality‐related topics were most often taught (51.5%), followed by urology (18%) and psychiatry (15%). Sexuality‐related topics were addressed mainly in classes on sexually transmitted diseases and AIDS (62.4%) and on the anatomy and physiology of the reproductive system (55.4%). About 25% of the professors reported teaching courses with a sexuality‐related title. There was emphasis on the impact of diseases and sexual habits (87.9%) and sexual dysfunction (75.9%). Less than 50% of professors addressed nonnormative sexuality or social aspects of sexuality. Conclusions: The teaching of sexuality in Brazilian medical schools occurred in a nonstandardized and fragmented fashion across several disciplines. The topic was incorporated with an organic and pathological bias, with a weak emphasis on the social aspects of sexuality and the variety of human sexual behaviors. The results point to the need for change in the provision of sexuality education in Brazilian medical schools.